S-nitrosylation-triggered secretion of mycobacterial PknG leads to phosphorylation of SODD to prevent apoptosis of infected macrophages - Saradindu Saha; Sadhana Roy; Arnab Hazra; Debayan Das; Vimal Kumar; Amit Kumar Singh; Ajay Vir Singh; Rajesh Mondal; Somdeb Bose Dasgupta (Proceedings of the National Academy of Sciences, 2025)
The tuberculosis-causing agent Mycobacterium tuberculosis (M.tb) establishes its niche inside macrophages by secretion of several virulence factors and engaging many host factors. Mycobacterial infection of macrophages results in a proinflammatory trigger–mediated secretion of TNFα. Protein kinase G (PknG), a Serine/Threonine kinase, is essential for mycobacterial survival within the macrophage. Pathogenic mycobacteria, upon infection, can trigger the secretion of proinflammatory cytokine TNFα, but whether secreted PknG plays any role in TNFα secretion at early stages of infection remains undeciphered. Moreover, at early infection stages, prevention of macrophage apoptosis is vital to successful mycobacterial pathogenesis. Our studies show that mycobacteria-secreted PknG can dampen the expression and concomitant secretion of proinflammatory TNFα. During early infection, M.tb infection–induced generation of reactive nitrogen intermediates (RNI) leads to S-nitrosylation of PknG on Cys109, thereby enabling its secretion into macrophages. Upon M.tb infection, secreted S-nitrosylated PknG phosphorylates macrophage Silencer of Death Domains (SODD) at Thr405, as identified through our phosphoproteomic studies. Thereafter, phosphorylated SODD, through an irreversible binding with the TNFR1 death domain, prevents Caspase8 activation and concomitant extrinsic apoptotic trigger. Moreover, alveolar macrophages from mice infected with PknG-knockout M.tb also exhibited SODD phosphorylation and hindered Caspase8 activation to prevent extrinsic macrophage apoptosis. Therefore, this work exhibits S-nitrosylation-mediated secretion of PknG to induce phosphorylation of macrophage SODD, which, through irreversible interaction with TNFR1, prevented extrinsic macrophage apoptosis at the early stages of infection.